The Role of Bhabinkamtibmas Malang City Polresta in the Framework of Harkamtibmas Post Kanjuruhan Riot - H. , M. Goldhie Arsy W. (Indonesian Journal of Police Studies, 2024)
The Kanjuruhan riot incident not only resulted in fatalities and injuries, but also triggered security and social security vulnerabilities. After this incident, the number of cases of disturbances to public peace/order in the Malang City Police jurisdiction showed a quite significant increasing trend. This demands the role of Bhabinkamtibmas as an element implementing Polri's duties in the field of community development, fostering and growing public awareness of laws and regulations as well as empowering the community's potential in preventing disturbances to Kamtibmas. In carrying out the task of community development in the context of social security and law and order after the Kanjuruhan riots, Bhabinkamtibmas not only plays a role in carrying out door to door system visits and counseling on social security and order to the community, but also establishes partnerships with all elements of society to play an active role in overcoming social problems that can trigger disruption of social security and social order. To analyze the role of Bhabinkamtibmas in the framework of social security and law and order after the Kanjuruhan riots, researchers used qualitative research methods, with a descriptive analysis approach. The research location is in the Malang City Police jurisdiction, with primary data sources obtained from interviews and observations as well as testing the validity of the data using triangulation of sources, techniques and time. The theoretical approach uses role theory, competency theory and cooperation theory. Based on the results of research and interviews with research objects, it is known that the role of Bhabinkamtibmas in the framework of public security and law and order after the Kanjuruhan riots is felt to be less intensive. This is indicated by the uneven competency of Bhabinkamtibmas in the ranks of the Malang City Police, lack of intensive door-to-door outreach activities and guidance on Kamtibmas counseling and the lack of partnership with the community in overcoming potential disturbances to Kamtibmas.